Environmental impacts on gneiss mineral exploration in João Baptista Eusébio Quarry in Anchilo – Nampula – Mozambique (Revista Brasileira Multidisciplinar, 2019)
The research analyzes the main environmental impacts from the industrial extraction of gneiss for civil construction in the city of Nampula. It´s looking for possible solutions to minimize the negative effects, by means of the adoption of technicians of extraction cleaner and sustainable. The gneiss is the object in study, a protolyte of granite, composed of quartz, feldspar and mica. The study was applied the bibliographic and experimental methods and observation, description and interview technicians. The not observe the law mining and environmental in Mozambique has contributed to a more irrational exploitation of the gneiss in Nampula. It causes high risk of increasing environmental degradation, characterized by change of the local ecosystem because of exposed to dust, gases and noise that affect the physical, biotic and anthropic surroundings.
Keywords: Mineral exploitation; Gneiss; Environmental impact